A Rare Component of Psammomatous Meningioma in a Testicular Teratoma - Fábio Meira Castro Pereira; Marbele Guimarães de Oliveira; Laiana do Carmo Almeida; Bruno Cunha Pires; José de Bessa Júnior (Case Reports in Pathology)
We report a case of a psammomatous variant of meningioma arising in a pure and mature testicular teratoma. At immunohistochemistry, the meningiomatous component showed epithelial membrane antigen, S100 protein, and vimentin positive. Benign neoplasms arising in testicular teratomas are extremely rare. To our knowledge, we have not found any such report of psammomatous variant of meningioma in a testicular teratoma and any meningioma arising in a pure and mature testicular teratoma. This is a unique phenomenon.